Mitochondrial NAD(P)H In vivo: Identifying Natural Indicators of Oxidative Phosphorylation in the 31P Magnetic Resonance Spectrum - Conley, Kevin E.; Ali, Amir S.; Flores, Brandon; Jubrias, Sharon A.; Shankland, Eric G. (Frontiers in Physiology, 2016)
Natural indicators provide intrinsic probes of metabolism, biogenesis and oxidative protection. Nicotinamide adenine dinucleotide metabolites (NAD(P)) are one class of indicators that have roles as co-factors in oxidative phosphorylation, glycolysis, and anti-oxidant protection, as well as signaling in the mitochondrial biogenesis pathway. These many roles are made possible by the distinct redox states (NAD(P)+ and NAD(P)H), which are compartmentalized between cytosol and mitochondria. Here we provide evidence for detection of NAD(P)+ and NAD(P)H in separate mitochondrial and cytosol pools in vivo in human tissue by phosphorus magnetic resonance spectroscopy (31P MRS). These NAD(P) pools are identified by chemical standards (NAD+, NADP+, and NADH) and by physiological tests. A unique resonance reflecting mitochondrial NAD(P)H is revealed by the changes elicited by elevation of mitochondrial oxidation. The decline of NAD(P)H with oxidation is matched by a stoichiometric rise in the NAD(P)+ peak. This unique resonance also provides a measure of the improvement in mitochondrial oxidation that parallels the greater phosphorylation found after exercise training in these elderly subjects. The implication is that the dynamics of the mitochondrial NAD(P)H peak provides an intrinsic probe of the reversal of mitochondrial dysfunction in elderly muscle. Thus, non-invasive detection of NAD(P)+ and NAD(P)H in cytosol vs. mitochondria yields natural indicators of redox compartmentalization and sensitive intrinsic probes of the improvement of mitochondrial function with an intervention in human tissues in vivo. These natural indicators hold the promise of providing mechanistic insight into metabolism and mitochondrial function in vivo in a range of tissues in health, disease and with treatment.